Legislative Coalitions in Presidential Systems: The Case of Uruguay. (15th February 2013) - Zucco, Cesar
ABSTRACT The article analyzes executive‐legislative relations in Uruguay between 1985 and 2005. It demonstrates that even after controlling for ideological affinity and acknowledging that ideology affects presence in the cabinet, legislators whose factions hold ministerial positions behave in a more progovernment way than their ideology would predict. This result not only shows that coalitions "work" but suggests that they work because the presidents use resources under their control to attract support from legislators. This article presents a systematic analysis of executive‐legislative relations in multiparty settings that builds on the finding that nonideologically contiguous coalitions often form to separate the ideological from the strategic determinants of legislative behavior. It also contributes to the literature by presenting a new set of roll call data and, more generally, highlights the risks of attempting to infer ideology directly from legislative behavior in presidential multiparty settings.